Circles of the Russian Revolution
1 online resource.
Keywords: "This volume provides the English-speaking reader with little-known perspectives of Central and Eastern European historians on the topic of the Russian Revolution. Whereas research into the Soviet Union's history has flourished at Western universities, the contribution of Central and Eastern European historians, during the Cold War working in conditions of imposed censorship, to this field of academic research has often been seriously circumscribed. Bringing together perspectives from across Central and Eastern Europe alongside contributions from established scholars from the West, this significant volume casts the year 1917 in a new critical light"--